Efficiency of cement-admixture systems in mortars with binary and ternary Portland cements (2018)
Compared to conventional concrete, high-performance concrete production offers such benefits as greater ease of placement, smaller sections, improved finishing and higher strength and durability. For the design of these types of concretes, it is advisable to carry out studies on pastes or mortars in order to evaluate admixture - cementitious material compatibility. This evaluation entails verifying fresh state properties and evolution over time. The aim of this work is to evaluate the behavior of mortars made with different water reducers as well as binary and ternary cements, and their connection to the properties they acquire in hardened state. Fluidity in the fresh state and absorption, density and compressive strength in the hardened state were evaluated. The results show that the impact of superplasticizers is not restricted to the fresh state, as influence on the development of the degree of hydration and compacity can also be noticed.